The Interrelationship of Business Strategy and Capital Structure with Corporate Profitability - Kurniawati, Hasni Dyah (Universitas Syiah Kuala, 2025)
This study explores the interrelationship between business strategy, capital structure, and corporate profitability through a qualitative approach using systematic literature review. The research aims to analyze how strategic typologies and financing decisions influence firm performance, both individually and interactively. Data were collected from forty peer-reviewed journal articles published between 2015 and 2024, sourced from reputable databases such as Scopus, Web of Science, and ScienceDirect. A thematic analysis method was employed to identify key patterns, theoretical insights, and contextual differences across industries and regions. The findings indicate that business strategy has a direct influence on profitability, particularly when firms adopt proactive and adaptive strategic orientations. Meanwhile, capital structure contributes to profitability based on the suitability of debt or equity with the firms strategic direction. The alignment between strategy and capital structure is shown to enhance profitability, especially when adjusted to the firms operational context and market dynamics. The study also highlights a research gap in integrated models, especially within emerging market contexts. It concludes that viewing strategy and finance as interdependent elements is essential for achieving sustained profitability. The findings provide a theoretical foundation for future empirical research and practical guidance for strategic-financial alignment in corporate decision-making.